Determinant Earnings Quality and Its Impact on Firm Value - Wibisono, Muhamad Gunawan; Andesto, Ronny (Green Publisher Indonesia, 2023)
This study aims to examine and analyze the effect of interest rates, inflation, foreign exchange rates and profitability on earnings quality and its impact on firm value. The design of this study used causal research with a population of banking subsector companies listed on the Indonesia Stock Exchange for the period 2018-2022. The sample in this study was 41 companies determined using the purposive sampling method. The data analysis method used is multiple linear regression analysis using E- views version 12. The results of this study show that interest rates, foreign exchange rates, and profitability have a significant negative effect on earnings quality, but inflation has no effect on earnings quality. Interest rates, inflation, foreign exchange rates, earnings quality have no effect on firm value, but profitability has a significant negative effect on firm value, interest rates, inflation, foreign exchange rates, and profitability have no effect on firm value through earnings quality.